Postpericardiotomy syndrome in pediatric heart transplant recipients. Immunologic characteristics. - Cabalka, A K (1995)
Clinical features of postpericardiotomy syndrome (PPS) occur in pediatric heart transplant recipients despite immunosuppression, which raises questions about the mechanism of PPS. We studied the clinical and immunologic characteristics of 15 pediatric heart transplant patients, ages 1.1 to 17.8 years (mean, 7.5 years); 7 had clinical evidence of PPS (PPS+), and 8 were without clinical features of PPS (PPS-). Indicators of PPS included fever, irritability, pericardial friction rub, leukocytosis without other cause, and pericardial effusion. The onset of PPS was from 9 to 26 postoperative days (mean, 16 days). Immunosuppressive regimens were comparable up to the day of PPS diagnosis in PPS+ patients, and up to day 16 in PPS- patients (average onset of PPS in PPS+ patients). No differences were found between groups with respect to weight-adjusted dosages of cyclosporin A, azathioprine, or corticosteroids. Mean cyclosporin A levels in PPS+ and PPS- patients were 142 +/- 88 ng/mL (mean +/- standard deviation) and 265 +/- 122 ng/mL (p = 0.045), respectively. Echocardiographic data on 3 PPS+ patients within 1 day of PPS diagnosis revealed pericardial effusions ranging from 5 to 24 mm. No data were available on the remaining 4 PPS+ patients. Minimal pericardial effusions (< 10 mm) were seen in 4 PPS- patients during a comparable time period. One PPS- patient required pericardiocentesis. Endomyocardial biopsy rejection grade did not differ between groups. Means pretransplant soluble interleukin-2 receptor levels did not differ between PPS+ and PPS- patients (758 +/- 410 vs 653 +/- 270 IU/mL); nor did the PPS+ pretransplant levels differ from levels obtained 1 or 2 months postoperatively (700 +/- 437 and 751 +/- 367 IU/mL, respectively). Although pretransplant percentages of the standard T-cell (CD2, CD3, CD4, CD8) and B-cell (DR and CD19) markers differed from post-transplant values, the changes could be explained by the immunosuppressive regimen and did not differ between PPS+ and PPS- patients. In the PPS+ patients, however, there were significant increases in the proportion of activated helper T cells (CD4+/25+) and cytotoxic T cells (Leu-7+/CD8+) following heart transplantation in comparison with pretransplant levels. We speculate that these changes in activation marker in PPS+ patients suggest a possible role for cell-mediated immunity in the pathogenesis of PPS in this group of patients.